Hepatocellular carcinoma tumour burden score to stratify prognosis after resection. Issue 7 (14th February 2020) - Tsilimigras, D I; Moris, D; Hyer, J M; Bagante, F; Sahara, K; Moro, A; Paredes, A Z; Mehta, R; Ratti, F; Marques, H P; Silva, S; Soubrane, O; et al.
Abstract: Background: Although the Barcelona Clinic Liver Cancer (BCLC) staging system has been largely adopted in clinical practice, recent studies have emphasized the need for further refinement and subclassification of this system. Methods: Patients who underwent hepatectomy with curative intent for BCLC-0, -A or -B hepatocellular carcinoma (HCC) between 2000 and 2017 were identified using a multi-institutional database. The tumour burden score (TBS) was calculated, and overall survival (OS) was examined in relation to TBS and BCLC stage. Results: Among 1053 patients, 63 (6·0 per cent) had BCLC-0, 826 (78·4 per cent) BCLC-A and 164 (15·6 per cent) had BCLC-B HCC. OS worsened incrementally with higher TBS (5-year OS 77·9, 61 and 39 per cent for low, medium and high TBS respectively; P < 0·001). No differences in OS were noted among patients with similar TBS, irrespective of BCLC stage (61·6 versus 58·9 per cent for BCLC-A/medium TBS versus BCLC-B/medium TBS, P = 0·930; 45 versus 13 per cent for BCLC-A/high TBS versus BCLC-B/high TBS, P = 0·175). Patients with BCLC-B HCC and a medium TBS had better OS than those with BCLC-A disease and a high TBS (58·9 versus 45 per cent; P = 0·005). On multivariable analysis, TBS remained associated with OS among patients with BCLC-A (medium TBS: hazard ratio (HR) 2·07, 95 per cent c.i. 1·42 to 3·02, P < 0·001; high TBS: HR 4·05, 2·40 to 6·82, P < 0·001) and BCLC-B (high TBS: HR 3·85, 2·03 to 7·30; P < 0·001) HCC. TBS could also stratify prognosis among patients in an external validation cohort (5-year OS 79, 51·2 and 28 per cent for low, medium and high TBS respectively; P = 0·010). Conclusion: The prognosis of patients with HCC varied according to the BCLC stage but was largely dependent on the TBS. Graphical Abstract: The prognosis of patients with hepatocellular carcinoma varied according to the Barcelona Clinic Liver Cancer (BCLC) stage; yet, it was largely dependent on the tumour burden score (TBS). Following resection, patients with similar TBS had comparable long-term outcomes, regardless of BCLC status, suggesting the need for further subclassification of the current BCLC guidelines and refinement of the proposed treatment algorithm using an assessment of total tumour burden. Added value